DETERMINANTS OF ECONOMIC GROWTH IN BOSOWASI DISTRICTS - Dedi Mardianto; Abdul Wahab; Siradjuddin (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Economic growth refers to efforts to increase the capacity for producing goods and services in order to achieve higher output, which is measured using the Gross Domestic Product (GDP) or the Gross Regional Domestic Product (GRDP) within a specific region. Therefore, the purpose of this study is to analyze the effect of unemployment, poverty, and per capita expenditure on economic growth in BOSOWASI, using cross-section and time series data from 2014 to 2023 obtained from the Central Bureau of Statistics (Badan Pusat Statistik/BPS). The method used in this study is quantitative, employing a panel data regression analysis approach. The results show that, partially (t-test), the variables unemployment and poverty have a negative but insignificant effect, while per capita expenditure has a positive and significant effect on economic growth in BOSOWASI. However, simultaneously (F-test), the variables unemployment, poverty, and per capita income have a significant effect on economic growth. These findings indicate that the government must continue to enhance productive activities to sustain and improve existing economic growth, thereby addressing and overcoming the challenges and issues in regional economic development.